1991
DOI: 10.1111/j.1365-2044.1991.tb09930.x
|View full text |Cite
|
Sign up to set email alerts
|

Day case laparoscopy: a survey of postoperative pain and an assessment of the value of diclofenac

Abstract: SummaryA randomised, controlled study was undertaken to assess the postoperative pain and side effects experienced by patients undergoing day case diagnostic laparoscopy and laparoscopic sterilisation, and to evaluate the effectiveness in these patients of peroperative diclofenac. Patients undergoing laparoscopic sterilisation had significantly higher pain scores at one hour postoperatively, and at discharge, than patients undergoing diagnostic laparoscopy ( p < 0.01 ) but there were no significant diferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
4
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 7 publications
2
58
4
1
Order By: Relevance
“…Clinical experience and other studies [5,6] have shown greater analgesic requirements and pain scores after laparoscopic sterilisation than after diagnostic laparoscopy. Thus this study was designed to assess the efficacy of a single pre-operative dose of morphine given by mouth in a randomised, double-blind, placebo-controlled trial in patients undergoing diagnostic laparoscopy and laparoscopic sterilisation.…”
mentioning
confidence: 87%
“…Clinical experience and other studies [5,6] have shown greater analgesic requirements and pain scores after laparoscopic sterilisation than after diagnostic laparoscopy. Thus this study was designed to assess the efficacy of a single pre-operative dose of morphine given by mouth in a randomised, double-blind, placebo-controlled trial in patients undergoing diagnostic laparoscopy and laparoscopic sterilisation.…”
mentioning
confidence: 87%
“…during surgery provides analgesia following dental surgery [9] but corroborates its demonstrated lack of efficacy for the pain following tonsillectomy [42]. When given rectally, however diclofenac is efficacious in reducing pain after tonsillectomy [43,44] and adenoidectomy [45], though its use by the intramuscular route after a variety of surgeries (hip, abdominal, dental) is both efficacious [46,47] and inefficacious [48,49]. Collated with these contradictory reports our findings suggest that the effect of diclofenac may be related to its route of administration and to the nature of surgery.…”
Section: Discussionmentioning
confidence: 93%
“…Spasmodic/cramping pain is the third type of pain, and hardly ever lasts longer than three to four hours (Dobbs et al, 1987;Edwards et al, 1991;Guard & Wiltshire, 1996). The take-home questionnaire revealed that eight subjects (six hours after surgery), four subjects (24 hours), and five subjects (48 hours) reported abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Given immediately prior to the surgical procedure, ketorolac will have a peak action in the postoperative period. However, it was shown to be less effective in decreasing postoperative pain following laparoscopic tub'al ligation (Edwards, Barclay, Catling, Martin & Morgan, 1991;Crocker & Paech, 1992;Shapiro & Duffy, 1994). This may in part be a result of the differences in pain experienced from the various types of laparoscopic procedures available for tubal sterilization.…”
Section: Laparoscopic Tubal Ligation Painmentioning
confidence: 99%